2013
DOI: 10.1039/c2cp43666c
|View full text |Cite
|
Sign up to set email alerts
|

Correlating the excited state relaxation dynamics as measured by photoluminescence and transient absorption with the photocatalytic activity of Au@TiO2core–shell nanostructures

Abstract: The spectroscopic and photocatalytic properties of a series of Au@TiO(2) core-shell nanostructures are characterized. The crystallinity of the TiO(2) shells was varied by changing the etching and calcination conditions. Measurements of the photoluminescence, transient absorption, and H(2) production rate permit us to look for correlations between the spectroscopic and catalytic behaviors. We found that there is a strong effect of crystallinity on the H(2) production rate and also the stretched exponential life… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
51
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(54 citation statements)
references
References 57 publications
3
51
0
Order By: Relevance
“…A recent study from our laboratory using well-defined Au@Void@TiO 2 yolk-shell nanostructures identified clear correlations among the lifetime of the fluorescence decay, the rate at which hydrogen is produced in photocatalysis, and the crystallinity of the titania shells: the more crystalline catalysts display both longer fluorescence lifetimes and higher hydrogen production rates (Fig. S1) (19). Surprisingly, however, similar fluorescence decay kinetics were seen here with Au@Void@TiO 2 versus Void@TiO 2 samples [ Fig.…”
Section: Resultsmentioning
confidence: 63%
“…A recent study from our laboratory using well-defined Au@Void@TiO 2 yolk-shell nanostructures identified clear correlations among the lifetime of the fluorescence decay, the rate at which hydrogen is produced in photocatalysis, and the crystallinity of the titania shells: the more crystalline catalysts display both longer fluorescence lifetimes and higher hydrogen production rates (Fig. S1) (19). Surprisingly, however, similar fluorescence decay kinetics were seen here with Au@Void@TiO 2 versus Void@TiO 2 samples [ Fig.…”
Section: Resultsmentioning
confidence: 63%
“…18,30,31,34,39 Since smaller metal particles can provide larger specic active sites, we synthesized Au NPs with 3-5 nm diameter by NaBH 4 reduction method using Au precursor (HAuCl 4 ) with weak capping agent (TSC). 18,30,31,34,39 Since smaller metal particles can provide larger specic active sites, we synthesized Au NPs with 3-5 nm diameter by NaBH 4 reduction method using Au precursor (HAuCl 4 ) with weak capping agent (TSC).…”
Section: Resultsmentioning
confidence: 99%
“…Although TSC-stabilized Au NPs (Au NPs-TSC) can be dispersed in DI water, Au NPs-TSC can be easily aggregated by changing the solution environment. 18,34,43,45 The reddish color of the PVP-treated Au NPs (Au NPs-PVP) solution was maintained and the UV-Vis absorption peak shi of the Au NP solution was negligible even aer adding NaBH 4 solution, indicating the well maintained stability (Fig. S1(a), † the original reddish color of the as-synthesized Au NPs-TSC solution was changed to dark violet by adding NaBH 4 solution (which is similar to the conditions of catalytic 4-NP reduction), indicating the instability of the Au NPs and their irreversible aggregation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[24a] All the three TiO 2 films' PIA show ultrafast rise indicating the highly efficient trapping of photoexcited electrons. The decay of the PIA signal is attributed to electron‐hole recombination . As the recombination is rate‐limited by a distribution of trap states, we fit the dynamics within 1 ns delay using a stretched exponential decay function (with an offset B to account for the long‐lived recombination extending beyond the measurement window.…”
mentioning
confidence: 99%